Notes on Some Biological Aspects of Arctornis riguata Snellen (Lepidoptera: Lymantriidae) - HARI SUTRISNO; . SUPUTA; HARI PURNOMO; SISWO POLANDONO; CIPTO WALUYO; ROSICHON UBAIDILLAH; . DARMAWAN; . ISMAIL; IMAN HIDAYAT; NUNUK WIDYASTUTI (HAYATI Journal of Biosciences, 2013)
Arctornis riguata Snellen is one of lymantriids which attacked a vast range of mango trees in Probolinggo at the beginning of 2011. About 1.2% mango trees from nine sub-districts have been defoliated by the larvae of this species. The larvae of this genus have been reported to forage at Anacardiacea as well; however, they have never been reported to forage at cultivated mango trees in Indonesia. Since there is no biological information of this species, thus, a study on some biological aspects of this species is needed. This study was conducted in the field as well as in the laboratory during 4 months (March-July 2011). The diagnostic characters of this species are black scale at dorsal antenna on both male and female and slightly setae particularly at the costal angle of valve on the male genitalia. Life span of this species is in the range of 30-37 days. This study also found four natural enemies of A. riguata i.e.: Bleparipa sp. (Diptera: Tachinidae), Euagathis sp. (Hymenoptera: Brachonidae), Theronia sp. (Hymenoptera: Ichneumonidae), and Brachymeria lasus (Hymenoptera: Chalcididae). Moreover, a single fungal pathogen of this species also was identified, i.e. Isaria fumosorosea Wize. Having these results, we considered that to control A. riguata, one need to conserve the native natural enemies by manipulating their environment.